Evaluation of modified Cam-Clay constitutive model in FLAC and its development by FISH programming. Issue 2 (28th January 2021) - Heidarzadeh, Heisam
Abstract: FLAC, Fast Lagrangian Analysis of Continua, is a numerical application (software) for analysing geotechnical structures using the finite difference method. It is one of the most popular numerical codes in geotechnical engineering used by various authors in literature. An appropriate way to apply constitutive models in a numerical analysis software is one of the most important issues that should be given special attention. In this article, the issues related to the Modified Cam-Clay (MCC) constitutive model is discussed; and a correct way to use it in FLAC is expressed. For this purpose, the MCC constitutive model pre-existing in FLAC has been criticised and revised by means of FISH programming in FLAC. It has been illustrated that the MCC pre-existing in FLAC has some disadvantages. This defect has been removed in the MCC constitutive model re-written by FISH in FLAC. Also, a novel and general concept of over-consolidation is introduced. Besides, a numerical model of a strip foundation on a clayey soil has been built and evaluated. In this way, the performances of the MCC constitutive model pre-existing in FLAC and the one re-whiten by FISH in FLAC have been compared and considered.